The Decalogue and African Moral Governance: Ethical Reflections on Religion and Public Policy - Michael, Nwulu Nwoko (FISIP UIN Sunan Gunung Djati Bandung, 2025)
Research Problem: African societies are characterized by complex intersections between indigenous traditions and external religious influences, particularly Christianity. The Decalogue (Ten Commandments), introduced through missionary and colonial encounters, has profoundly shaped moral consciousness and legal norms across the continent. However, its integration has also produced tensions between traditional African values and Western ethical paradigms, raising questions about how moral frameworks rooted in religion influence social governance and public policy in Africa. Research Purposes: This study aims to examine the impact of the Decalogue on African moral and social polity, with particular attention to its role in shaping ethical principles, family structures, and communal life. It also seeks to explore how Decalogue-based morality can contribute to inclusive, culturally sensitive public policy in contemporary African societies. Research Methods: The study adopts a qualitative, interpretive approach, analyzing secondary data from theological literature, historical records, and socio-political commentaries. Using interdisciplinary perspectives from ethics, religious studies, and African philosophy, the paper investigates how the Decalogue has been contextualized within African worldviews and its implications for governance and moral policy.. Results and Discussion: Findings reveal that the Decalogue has significantly influenced African moral and legal norms, reinforcing values such as justice, honesty, respect for life, and communal harmony. Yet, its colonial transmission introduced cultural and ethical dissonance, often positioning Western Christian morality as superior to indigenous systems of ethics. Despite this tension, African societies have demonstrated adaptive resilience, blending biblical moral codes with traditional communal ethics to produce hybrid models of governance and moral practice. Research Implications and Contributions: This study underscores the need for contextually grounded moral frameworks that harmonize Decalogue-based ethics with African cultural values. It contributes to the discourse on religion and public policy by advocating for culturally sensitive moral governance that promotes peace, justice, and human dignity. The research also highlights the importance of sustained interfaith dialogue between African Traditional Religion and Christianity as a pathway toward inclusive moral policymaking and sustainable social development.